Analysis of notified drug poisoning among children in Santa Catarina state, 2016-2020 - Karoliny Brock; Gabriel Oscar Cremona Parma; Alessandra de Sá Soares; Fabiana Schuelter-Trevisol (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: The aim of this study was to analyze the incidence of drug poisoning in children registered in the Santa Catarina Information and Toxicological Assistance Center between 2016 and 2020. Methods: This observational epidemiological study, with a historical cohort design, was carried out from reported cases of drug poisoning in children aged 0-12 years. Census sampling was used to collect data. Results: There were 4839 reported cases of drug poisoning among children in the State of Santa Catarina in the surveyed period, with an average annual incidence rate of 6 cases/1000 live births. The median age was 3 years. Most cases of poisoning occurred among girls aged 0-3 years by accidental ingestion of drugs at home. There was a predominance of signs and symptoms affecting the nervous system; only a small portion required hospitalization. Most cases were considered mild poisoning with a favorable outcome. No deaths were recorded. There was a tendency of increasing cases over time, however not significant. There is a predominance of incident cases in the Great West of the state, followed by the Midwest and Serra Catarinense regions. Conclusions: Drug poisoning in children is predominant in early childhood, mainly caused by accidental ingestion of drugs at home. These findings highlight the importance of preventive and educational measures among family members and caregivers.